Association of growth hormone (GH) gene polymorphism with growth and carcass in Sumba Ongole (SO) cattle - Agung, P. P.; Anwar, S.; Putra, W. P. B.; Zein, M. S. A.; Wulandari, A. S.; Said, S.; Sudiro, A. (Diponegoro University, 2017)
A study was conducted to identify the polymorphism in the intron 3 of the Growth Hormone (GH) gene and also to evaluate the association of the GH gene polymorphism with growth parameters and dressing percentage in the Sumba Ongole (SO) cattle. A total of 267 individual DNA samples were used in the Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP) analysis. The SO cattle growth parameters data (n=44) including birth weight (BW), weaning weight at 205 days of age (WW205), yearling weight at 365 days of age (YW365) and also dressing percentage (DP) (n=122) were investigated in this study. There were three genotypes (AA, AB, and BB) of the GH gene based on the PCR-RFLP analysis with allele frequency was 0.87 and 0.13 for A allele and B allele respectively. The highest genotype frequency in the SO cattle is AA (0.76) and the lowest is BB (0.02). The Heterozygosity Observed (Ho) value in the SO cattle population is 0.23 and Polymorphism Information Content (PIC) value is 0.20. Therefore, the genetic diversity in the SO cattle based on the GH gene polymorphism is quite low. There is no association (P>0.05) in BW, WW205, YW365, and DP with genotypes of the GH gene. As the result, the GH gene in this study cannot be used as a genetic marker in the SO cattle breeding program.